The Influence of Workload, Work Motivation, and Organizational Citizenship Behavior on Job Satisfaction inPT Pertamina (Persero) Refinery Unit (Ru) VI Balongan - Yuliani, Selfi; Afiah, Afwa; Maryam, Siti (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This research is motivated by the importance of increasing employee job satisfaction, because currently there are many problems that can affect job satisfaction such as workload that exceeds capacity or ability, low work motivation and suboptimal performance, and the need for organizational citizenship behavior in supporting company quality. By understanding the relationship between these three factors, companies can create more effective strategies, appropriate policies, and ideal work procedures so that optimal job satisfaction can be achieved. This study reveals the influence of workload, work motivation, and Organizational Citizenship Behavior (OCB) on job satisfaction. Design/methodology/approach: With a 5% margin of error and the Slovin formula, 110 individuals were sampled for the study. Simple random sampling was employed, and questionnaires were distributed to gather data. The data were analyzed using multiple linear regression via SPSS 25.0 apk. Findings: Both workloadsby the sig. value of0.813 > 0.05and work motivationby the sig. value of0.054 > 0.05did not significantly affect job satisfaction, according to the results. But it turned out that OCB had a big impact on job satisfactionby the sig. value of0.000 < 0.05. Overall, a significant relationship was found between workload, work motivation, and OCB with employee job satisfactionby the F value of10,197 andsig. of0.000 < 0.05. Paper type: Research paper.